Performance comparison of electro-polymerized polypyrrole and polyaniline as cathodes for iodine redox reaction in zinc-iodine batteries. (20th May 2022) - Miao, Xiaofei; Chen, Qi; Liu, Yongchuan; Zhang, Xiangxin; Chen, Yuanqiang; Lin, Junhong; Chen, Sujing; Zhang, Yining
Highlights: Electropolymerized PANI and PPy serve as cathode for Zn//I battery, respectively. The PANI shows a micro-nano porous structure while the PPy is dense. The porous PANI has more excellent electrochemical performances than the PPy. The performance differences are related to the microstructure of the PANI and PPy. The PANI electrode has a 75.7% capacity retention after 10, 000 cycles at 3.5 A g −1 . Abstract: At present, Zinc-iodine (Zn//I) batteries have attracted much attention due to their high safety and capacity. However, how to suppress the shuttling of polyiodide ions generated during charging processes is still a tricky problem. Herein, polyaniline (PANI) and polypyrrole (PPy) are electro-polymerized on carbon felt (CF) by constant current and used as cathodes for zinc-iodine (Zn//I) batteries. Electrochemical tests of the PANI@CF and PPy@CF electrodes prove that the PANI@CF electrode has a higher capacity, a stronger ability to suppress shuttling of polyiodine ions, and more excellent cyclic stability than the PPy@CF electrode. According to the material characterizations, the differences of both electrodes in electrochemical performances are mainly caused by the microstructures of PANI and PPy in both electrodes. The PANI has a micro-nano porous structure while the PPy is very dense. The porous PANI not only has more channels for the infiltration of electrolyte, but also can provide more active adsorption sites to minimize the shuttling of polyiodide ions to anode, ensuring the excellent performances of the PANI@CF. However, dense PPy seriously hinders the electrolyte diffusion and triggers the formation of an insulating dense iodine film, bringing poor performances to the PPy@CF. Ultimately, the PANI@CF electrodes achieves the most specific capacity of 235.9 mAh g −1 at 0.35 A g −1 (∼1.7 C) and performs out long cycle life with high stability (75.7% capacitiy rention after 10, 000 cycles) at 3.5 A g −1 (∼17 C) in Zn//I battery, manifesting the porous PANI@CF electrode is a greatly promising candidate as cathode for Zn//I batteries in actual application.